CHINA FOREIGN POLICY: A LEGAL ANALYSIS - Ma Junyu (Jurnal Pembaharuan Hukum, 2022)
This study aims to find out China's foreign policy in carrying out its economy which is characterized by its own economy, as a communist country but China does not carry out a complete communist economic system. Since 1978 the Chinese government has reformed a more planned economic system which is more market oriented. Thus the higher-ups increased the power of local leaders and installed managers in industry, allowing small-scale enterprises in services and light production. This study uses qualitative research by collecting data sources in the literature and then analyzing them according to the research objectives. China also uses politics in its economic cooperation with other countries, namely by setting the condition that countries wishing to establish cooperation with China must agree to China's claims to Taiwan and sever official relations with the Taiwanese government. Data analysis shows that China's foreign policy making is still traditional communist style, which has continued its leadership from the beginning such as Mao Zhedong to Xi Jinping. China as a communist country with foreign policy makers centered on one central command. It can be interpreted that China's foreign policy is determined by the leader of the country and the people around him. The conclusion of this study is that in deciding a Chinese foreign policy through the Think Tank group or the Politburo in its government.